Effects of fatigue and surface instability on neuromuscular performance during jumping - Lesinski, M.; Prieske, O.; Demps, M.; Granacher, U. (Scandinavian Journal of Medicine & Science in Sports, 2016)
It has previously been shown that fatigue and unstable surfaces affect jump performance. However, the combination thereof is unresolved. Thus, the purpose of this study was to examine the effects of fatigue and surface instability on jump performance and leg muscle activity. Twenty elite volleyball players (18 ± 2 years) performed repetitive vertical double-leg box jumps until failure. Before and after a fatigue protocol, jump performance (i.e., jump height) and electromyographic activity of selected lower limb muscles were recorded during drop jumps (DJs) and countermovement jumps (CMJs) on a force plate on stable and unstable surfaces (i.e., balance pad on top of force plate). Jump performance (3-7%; P < 0.05; 1.14 = d = 2.82), and muscle activity (2-27%; P < 0.05; 0.59 = d = 3.13) were lower following fatigue during DJs and CMJs, and on unstable compared with stable surfaces during DJs only (jump performance: 8%; P < 0.01; d = 1.90; muscle activity: 9-25%; P < 0.05; 1.08 = d = 2.54). No statistically significant interactions of fatigue by surface condition were observed. Our findings revealed that fatigue impairs neuromuscular performance during DJs and CMJs in elite volleyball players, whereas surface instability affects neuromuscular DJ performance only. Absent fatigue × surface interactions indicate that fatigue-induced changes in jump performance are similar on stable and unstable surfaces in jump-trained athletes.